Exploring the potential association among sleep disturbances, cognitive impairments, and immune activation in 22q11.2 deletion syndrome. Issue 3 (14th December 2019) - Yirmiya, Erez T.; Mekori‐Domachevsky, Ehud; Weinberger, Ronnie; Taler, Michal; Carmel, Miri; Gothelf, Doron
Abstract: 22q11.2 deletion syndrome (22q11.DS) is a neurogenetic disorder caused by a microdeletion in chromosome 22. Its phenotype includes high rates of psychiatric disorders, immune system abnormalities, and cognitive impairments. We assessed the quality of sleep in 22q11.2DS and its potential link to inflammatory markers and cognitive deficits. Thirty‐three 22q11.2DS individuals and 24 healthy controls were studied. Sleep parameters were assessed by the Pittsburgh sleep quality index (PSQI) questionnaire and correlated with serum cytokine levels and cognitive functioning, measured using the Penn computerized neurocognitive battery (CNB). The 22q11.2DS individuals had significantly worse sleep quality scores than the controls, unrelated to the psychiatric or physical comorbidities common to 22q11.2DS. Interleukin 6 levels were correlated with the overall score of the PSQI questionnaire for nonpsychotic 22q11.2DS participants only. Several domains of the CNB were associated with poorer sleep quality, suggesting that cognitive impairments in 22q11.2DS may be at least partially explained by poor sleep quality. Our findings confirm sleep impairments in individuals with 22q11.2DS, which might negatively affect their cognitive functioning, and corroborate a potential role of immunological pathways in the 22q11.2DS neuro‐phenotype.